Preparation of alumina-coated graphite for thermally conductive and electrically insulating epoxy composites. Issue 68 (25th July 2015) - Tang, Dahang; Su, Juqiao; Yang, Qi; Kong, Miqiu; Zhao, Zhongguo; Huang, Yajiang; Liao, Xia; Liu, Ying
<x xml:space="preserve">Abstract</x> Volume resistivity of epoxy composites containing various fillers and amounts of filler particles.